2018
DOI: 10.1016/j.foodchem.2017.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with ethanol as an alternative to improve steviol glycosides extraction and purification from a new variety of stevia

Abstract: Leaves of a new variety of Stevia rebaudiana with a high content of rebaudioside A were pretreated with ethanol. The ethanolic extract showed high antioxidant potential and 39 compounds were identified, by UPLC/HRMS, among them one not yet mentioned in the literature for stevia leaves. From the in natura leaves and pretreated leaves, the conditions of aqueous extraction of steviol glycosides were investigated using response surface methodology. The aqueous extracts obtained were purified by ion exchange chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 29 publications
6
33
0
9
Order By: Relevance
“…44 Fourth, noting that misconceptions surrounding Stevia continue to slow progress in its uptake minimising the incidence of diabetes and obesity, 45 practitioners of the bioeconomy should be aware that progress in formulating sweeteners based on steviol glycosides has been so significant that today children prefer skim chocolate sweetened with a commercial Stevia sweetener white powder soluble in water produced from aqueous extract of Stevia leaves (95% on dry weight basis in steviol glycosides, Rebaudioside A plus Stevioside > 75%). As lately shown by Formigoni and co-workers in Brazil, 27 a simple treatment of the Stevia leaves with absolute ethanol before the aqueous extraction of steviol glycosides selectively removes the phenolic compounds and flavonoids which contribute to the residual bitter taste in the final product affording steviol glycosides whose sensory profile is similar (and better) to that of sucralose.…”
Section: Conclusion and Recommendationsmentioning
confidence: 91%
See 2 more Smart Citations
“…44 Fourth, noting that misconceptions surrounding Stevia continue to slow progress in its uptake minimising the incidence of diabetes and obesity, 45 practitioners of the bioeconomy should be aware that progress in formulating sweeteners based on steviol glycosides has been so significant that today children prefer skim chocolate sweetened with a commercial Stevia sweetener white powder soluble in water produced from aqueous extract of Stevia leaves (95% on dry weight basis in steviol glycosides, Rebaudioside A plus Stevioside > 75%). As lately shown by Formigoni and co-workers in Brazil, 27 a simple treatment of the Stevia leaves with absolute ethanol before the aqueous extraction of steviol glycosides selectively removes the phenolic compounds and flavonoids which contribute to the residual bitter taste in the final product affording steviol glycosides whose sensory profile is similar (and better) to that of sucralose.…”
Section: Conclusion and Recommendationsmentioning
confidence: 91%
“…Furthermore, sensorial evaluation demonstrated that the extract from pretreated leaves presented a sensory profile similar to that of synthetic sweetener sucralose, a chlorinated sugar, with the acceptance of the sweetener consumed by the treated leaves (7.00±1.95) even higher than that of the world's most used synthetic sweetener (6.33±1.72). 27 In detail, the sweetener obtained was 165 times sweeter than sucrose, and the bitterness threshold was 0.073 ±0.013 g/100 mL, considerably higher than the threshold of bitterness of stevioside (0.0172 ± 0.0050 g/100 mL) and stevioside enzymatically modified (0.0263 ± 0.0056 g/100 mL), therefore proving to be significantly less bitter.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Remarkably, from the point of view of the final use of the extract as natural sweetener, the scholars found that the antioxidant activity, phenolic compounds and flavonoids increased , whereas arachidic and beenic fatty acids were detected only in the leaves treated with EtOH. Furthermore, sensorial evaluation demonstrated that the extract from pretreated leaves presented a sensory profile similar to that of the synthetic sweetener sucralose, a chlorinated sugar, with the acceptance of the sweetener consumed by the treated leaves (7.00 ± 1.95) even higher than that of the world's most used synthetic sweetener (6.33 ± 1.72) …”
Section: Composition Analysis and Extraction Routesmentioning
confidence: 99%
“…Fourth, noting that misconceptions surrounding stevia continue to slow progress in its uptake, delaying an opportunity to minimize the incidence of diabetes and obesity, practitioners of the bioeconomy should be aware that progress in formulating sweeteners based on steviol glycosides has been so significant that today's children were found to prefer skim chocolate sweetened with a commercial stevia sweetener white powder soluble in water produced from aqueous extract of stevia leaves (95% on a dry weight basis in steviol glycosides, rebaudioside A plus stevioside >75%) . As shown recently by Formigoni's research team in Brazil, simple treatment of the stevia leaves with absolute ethanol before the aqueous extraction of steviol glycosides selectively removes the phenolic compounds and flavonoids that contribute to the residual bitter taste in the final product, resulting in steviol glycosides whose sensory profile is similar to (and better than) that of sucralose.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%